Coupled cluster methods for autoionisation resonances - Sajeev, Y.; Ghosh, A.; Vaval, N.; Pal, S. (International Reviews in Physical Chemistry, 2014)
The quantum chemical calculation of autoionisation resonances in many-electron systems is a highly challenging task due to the ionisation continuum involved. Recently, advances were reported where conventionally used ab initio codes can be employed to compute autoionisation resonances. This is made possible by the use of analytical continuation tools such as complex scaling and complex absorbing potential (CAP) in the electronic structure codes. We review the formulation and the use of complex scaling and CAP in coupled cluster methods for the electron correlated calculation of energy position and autoionisation decay rate of resonance states. The application of analytically continued coupled cluster method for the correlated calculation of interatomic or intermolecular Coulombic decay process is also discussed.
Keywords: autoionisation resonances; complex absorbing potential; complex scaling; equation-of-motion coupled cluster; Fock space multi-reference-coupled cluster; intermolecular Coulombic decay